Towards Resilience in Social Sciences - from Psychology to Social Pedagogy - Agnieszka Bzymek (The Francis de Sales Scientific Society (TNFS.PL), 2021)
In the view of recent social sciences, the concept of resilience is associated primarily with positive adaptation regarding people exposed to various adversities and traumatic events for both children and adults. The majority of researchers ultimately agree on the coexistence of several factors affecting the disruption of an individual's functioning, illness or social maladaptation. With reference to social pedagogy, the category of resilience being not only psychological, finds comprehensive application to human and social life, including social problems, social exclusion and threats regarding family, school and education environment, and, finally, assistance in development processes and education of adults and the elderly. The aim of the article is to point out the indicated aspects.